Optimal and Suboptimal Control of a Standard Brownian Motion - Lefebvre Mario (Archives of Control Sciences, 2016)
The problem of optimally controlling a standard Brownian motion until a fixed final time is considered in the case when the final cost function is an even function. Two particular problems are solved explicitly. Moreover, the best constant control as well as the best linear control are also obtained in these two particular cases.